PENGARUH KONSERVATISME AKUNTANSI TERHADAP RELEVANSI NILAI LAPORAN KEUANGAN, MANAJEMEN LABA DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI TAHUN 2016-2018) - Mohammad Alfin; Moh. Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
Accounting conservatism is a reaction that tends to be cautious in financial reporting that aims to make the financial statements produced by the company reflect the real condition of the company. This study was conducted to analyze the Effect of Accounting Conservatism on the Relevance of Financial Statements and Earnings Management with Managerial Ownership as a Moderation Variable. This method is determining the sample using purposive sampling, with several predetermined criteria, the total sample of 49 manufacturing companies listing on the Indonesia Stock Exchange in 2016 - 2018. Research data is secondary data obtained from the Indonesia Stock Exchange in 2016 - 2018. Technical Data analysis uses simple and multiple linear regression analysis. Based on the research carried out, it can be concluded that accounting conservatism has a significant influence on earnings management. Accounting conservatism has a significant influence on the value relevance of financial statements. Managerial ownership cannot influence the interaction of accounting conservatism on earnings management. Managerial ownership cannot influence the interaction of accounting conservatism on the value relevance of financial statements.Keywords: Accounting Conservatism The Value Relevance of Financial Statements, Earnings Management, Managerial Ownership